PELATIHAN DAN PENDAMPINGAN INSTAGRAM BAGI UMKM KOTA BOGOR UNTUK OPTIMALISASI PEMASARAN DIGITAL - Denta Purnama; Yulia Nurendah (Universitas Mataram, 2026)
In line with the rapid advancement of technology, both in terms of its development and utilization, Micro, Small, and Medium Enterprises (MSMEs) in Bogor City are required to adapt in order to effectively respond to technological changes that support their business activities. One critical aspect that must be considered is promotion. In the current digital era, promotional strategies need to be aligned with contemporary trends, particularly through the use of social media platforms such as Instagram, which offers significant potential as a promotional medium for MSMEs. This program aims to provide training on optimizing Instagram as a digital marketing tool for MSMEs in Bogor City. Furthermore, the program equips MSME actors with practical skills in content creation and effective account management on Instagram. The method employed in this program involves direct, hands-on training for MSME participants to address their limited understanding of Instagram optimization as a promotional medium. The training covers essential topics, including account creation, content development, and basic social media management strategies. The results of this program indicate that MSMEs in Bogor City are able to establish business-oriented Instagram accounts, produce more structured and engaging content, and implement more effective and sustainable social media management practices. This community service program, delivered in the form of digital marketing training, has contributed to enhancing the capacity of MSMEs, enabling them to remain competitive and sustain their businesses in an increasingly competitive market environment.